(untitled) (Medical Forum Monthly, 2025)
Objective: (1) To elicit evidence of new case detection in Basrah regarding hemoglobinopathy. (2) To study certain characteristics of the newly diagnosed cases. (3) To study characteristics of the newly registered patients in context of the premarital screening program issued since 6 years (4) To detect if the evidence of hemoglobinopathy within the families acts as a deterrent for the families from having further effected children. Study Design: Retrospective, single-center analysisPlace and Duration of Study: This study was conducted at the Basrah Center for Hereditary Blood Diseases, Basrah Iraq from 1st January 2024 to 31st December 2024. Methods: This retrospective, single-center analysis was conducted at Basrah Center for Hereditary Blood Diseases, Basrah Iraq vide letter No.18 dated 5th April 2023 and 508 individuals diagnosed with hemoglobinopathies were enrolled.Results: Sickle cell anemia and sickle β-thalassemia accounted for 31.3% and 34.8% of cases, respectively. Gender distribution was nearly equal across all types, reflecting the autosomal recessive inheritance pattern.Consanguineous marriage was reported in 62% of cases, with the highest familial relation seen among sickle cell anemia patients. Familial clustering was evident, with 144 patients having at least one affected sibling. Educational attainment was low, with 45.5% of patients being illiterate and only 5.1% holding a college degree. Conclusion: The strong influence of genetic, socio-cultural, and educational factors on hemoglobinopathy prevalence. The high rates of familial clustering and consanguinity highlight the urgent need for